2018
DOI: 10.1088/1612-202x/aacee5
|View full text |Cite
|
Sign up to set email alerts
|

An upper bound on the rate of information transfer in optical vortex beams

Abstract: Light endowed with orbital angular momentum, commonly termed optical vortex light, has an azimuthal phase indexed by the orbital quantum number l. In contrast to the two basis states of the optical spin angular momentum, the interest in the information content of optical vortex beams is centred on the assumption that |l forms a countably infinite set of basis states. The recent experimental observation that group velocity is inversely proportional to l provides a theoretical basis for a practical measure of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…the photon states detected by SPTM between a 1 and b 1 or between a 2 and b 2 , similar to |Φ ′ ⟩ 2 (3,4) and |Φ ′′ ⟩ 2 (3,4) . It can be found that channel noise does not reduce the fidelity of single-photon states, but change the probabilities of the photon exporting to according paths.…”
Section: High-capacity Information Transmission With Single-photon Ov...mentioning
confidence: 80%
See 1 more Smart Citation
“…the photon states detected by SPTM between a 1 and b 1 or between a 2 and b 2 , similar to |Φ ′ ⟩ 2 (3,4) and |Φ ′′ ⟩ 2 (3,4) . It can be found that channel noise does not reduce the fidelity of single-photon states, but change the probabilities of the photon exporting to according paths.…”
Section: High-capacity Information Transmission With Single-photon Ov...mentioning
confidence: 80%
“…The capacity and security of information transmission are important features in the communication process [1][2][3][4]. Quantum dense coding, which can transmit two bits of classical information by sending only one particle with a bipartite entangled state, is considered to be a protocol that can provide a more efficient and more secure information transmission [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We have aimed to show that developing and applying the full quantum theory in the description of optical interactions is relatively straightforward-and perhaps it is simpler than is commonly supposed. Moreover, beyond the applications we have illustrated here, it affords a robust framework for conceiving, explaining and understanding many more intricate processes-including those that hinge on the photon for quantum informatics [35,36]. In this paper, we have derived some of the simplest optical processes and provided some physical insights into what the theory show about them.…”
Section: Discussionmentioning
confidence: 97%
“…(although defining a quantum operator for the phase is well-known to be extremely problematic [75][76][77]). While achieving enhanced information content per photon can be exploited for data transmission at low values of the topological charge, there is an ultimate trade-off, where increasing the topological charge ceases to deliver any advantage [78]. The paraxial approximation is defensible only if allowance is made for an effective indistinguishability of photons with small differences in propagation direction, within a quantization volume V. If we consider two modes Ω and Ω of the same indices ( , p) but with small local differences in wave-vector direction, then developing the commutation equation in terms of cylindrical coordinates (see Figure 1b), we find [42]:…”
Section: Quantum Uncertaintymentioning
confidence: 99%